A Turbidity Test Based Centrifugal Microfluidics Diagnostic System for Simultaneous Detection of HBV, HCV, and CMV - Hung-Cheng Chang; Yu-Tin Chao; Jia-Yush Yen; Ya-Lin Yu; Chun-Nan Lee; Bing-Ching Ho; Kou-Chen Liu; Jiunn Fang; Chii-Wann Lin; Jiun-Haw Lee (Advances in Materials Science and Engineering)
This paper presents a LAMP- (loop-mediated isothermal amplification-) based lab-on-disk optical system that allows the simultaneous detection of hepatitis B virus, hepatitis C virus, and cytomegalovirus. The various flow stages are controlled in the proposed system using different balance among centrifugal pumping, Coriolis pumping, and the capillary force. We have implemented a servo system for positioning and speed control for the heating and centrifugal pumping. We have also successfully employed a polymer light-emitting diode section for turbidity detection. The easy-to-use one-click system can perform diagnostics in less than 1 hour.